Faktor Penyebab Ketidaklengkapan Pengisian Dokumen Rekam Medis Rawat Inap di Rumah Sakit - Alfiansyah, Gamasiano; Pratiwi, Dita Melinda; Nuraini, Novita; Nurmawati, Ida (FORIKES, 2022)
One of the characteristics of good medical record management is a complete medical record. This study aims to determine the factors causing the incomplete filling of inpatient medical record documents. The method used in this study was a literature review with 15 journal articles that had been selected according to the inclusion criteria. The results showed that there were several factors causing incomplete filling of inpatient medical record documents as seen from the